Empowering Students’ English-Speaking Skills through AI-Supported TikTok-Based Learning Platforms in MAN Labuhanbatu Utara - Syahrul Efendi Lubis; Gumarpi Rahis Pasaribu (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
This community service program aimed to empower students’ English speaking skills through the integration of AI-supported TikTok-based learning platforms at MAN Labuhanbatu Utara. The program involved 30 students and employed a participatory and practice-based approach focusing on active engagement and communicative language use. The activities were conducted through several stages, including needs analysis, implementation, and evaluation. During the implementation, students were guided to create short English speaking videos using TikTok supported by artificial intelligence features such as automated subtitles and pronunciation assistance. The results indicated noticeable improvements in students’ speaking fluency, pronunciation, confidence, and learning motivation. Students became more actively involved in speaking activities and demonstrated increased willingness to communicate in English. The use of AI-supported tools facilitated self-correction and autonomous learning, while TikTok created a low-anxiety and engaging learning environment. Overall, the program demonstrates that AI-supported TikTok-based learning platforms offer an innovative and effective approach to enhancing English speaking skills in a madrasah educational context.